Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada RM. Ayam Kampung Pinang Cabang Graha Raya Tangerang - Dimas Agung Prasetya; Haryantini Haryantini (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. RM. Ayam Kampung Pinang Cabang Graha Raya Tangerang, a culinary business, is committed to providing the best experience through high-quality dishes. In today’s intense culinary competition, product quality and price are among the factors that influence purchasing decisions. This study aims to determine the effect of product quality and price on purchasing decisions at RM. Ayam Kampung Pinang Cabang Graha Raya Tangerang. The research uses an associative quantitative method, with a total population of 24,945. The sample consisted of 100 respondents collected through questionnaires and determined using a non-probability sampling technique with an accidental sampling method. The data were analyzed using SPSS. The results show that product quality has a significant effect on purchasing decisions, as evidenced by the significance value (<0.001 < 0.05), the t-value (5.982 > 1.984), and an R Square of 0.280 (28%). In contrast, price has a negative and insignificant effect, with a significance value (0.746 > 0.05), a t-value (-0.325 < 1.984), and an R Square of 0.015 (0.15%). Furthermore, simultaneously, product quality and price have a positive and significant effect on purchasing decisions, as proven by the F-test results (F-value 18.911 > 3.939) and the significance value (<0.001 < 0.05). The simultaneous R Square value is 0.281, meaning that product quality and price contribute 28.1% to purchasing decisions, while the remaining percentage is influenced by other factors.